2001
DOI: 10.1007/s002390010149
|View full text |Cite
|
Sign up to set email alerts
|

Aquifex aeolicus 3-Deoxy-d-manno-2-Octulosonic Acid 8-Phosphate Synthase: A New Class of KDO 8-P Synthase?

Abstract: The relationship between 3-deoxy-D-manno-2-octulosonic acid 8-phosphate (KDO 8-P) synthase and 3-deoxy-D-arabino-2-heptulosonic acid 7-phosphate (DAH 7-P) synthase has not been adequately addressed in the literature. Based on recent reports of a metal requiring KDO 8-P synthase and the newly solved X-ray crystal structures of both Escherichia coli KDO 8-P synthase and DAH 7-P synthase, we begin to address the evolutionary kinship between these catalytically similar enzymes. Using a maximum likelihood-based gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 44 publications
2
62
0
Order By: Relevance
“…This unique feedback regulatory mechanism observed with the aroA and aroQ fusion proteins prompted us to re-examine the results from previous phylogenetic studies (8,9) that divided the microbial DAHPS family into two subfamilies. ClustalW (17) analysis of the amino acid sequence found that AroAI ␤ DAHPSs, to which aroA(Q) Bs and aroA(Q) Pg were assigned, appear to consist of two types of enzymes (Table 3), one with a shorter sequence defining a single DAHPS domain (type I, ϳ270 residues) and one with a longer sequence that contains a single DAHPS domain plus an extra segment with divergent sequences at either the N or C terminus (type II, ϳ350 residues).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This unique feedback regulatory mechanism observed with the aroA and aroQ fusion proteins prompted us to re-examine the results from previous phylogenetic studies (8,9) that divided the microbial DAHPS family into two subfamilies. ClustalW (17) analysis of the amino acid sequence found that AroAI ␤ DAHPSs, to which aroA(Q) Bs and aroA(Q) Pg were assigned, appear to consist of two types of enzymes (Table 3), one with a shorter sequence defining a single DAHPS domain (type I, ϳ270 residues) and one with a longer sequence that contains a single DAHPS domain plus an extra segment with divergent sequences at either the N or C terminus (type II, ϳ350 residues).…”
Section: Discussionmentioning
confidence: 93%
“…Previously, several biochemical properties (7,8) have been separately proposed as the possible criteria characterizing the individual subfamilies. Nevertheless, as discussed earlier, none of these suggestions have been demonstrated to be convincing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations